Aktivitas Antioksidan Hidrolisat Protein Ikan Cunang (Congresox talabon) - Anggi Angelita Hermaya; Edison Edison; Andarini Diharmi (Universitas Djuanda, 2021)
Cunang fish (Congresox talabon) has the potential as a raw material for fish protein hydrolyzates. Hydrolysis of cunang fish using the enzyme papain were produced peptides and amino acids that have antioxidant activity. The aim of this study was to determine the antioxidant activity of the protein hydrolyzate of cunang fish using different papain enzyme concentrations. This study used an experimental method with a completely randomized non-factorial design with three replications, with different papain enzyme concentrations (2%, 4%, 6%). The analysis parameters consisted of proximate content analysis in fish meat, degree of hydrolysis, the dissolved protein of the Bradford method, and the antioxidant activity of the DPPH method on the protein hydrolysate. The results showed that the protein content of cunang fish had 73.15% (bk). The papain enzyme concentration of 6% was the best concentration hydrolyze cunang meat, is produced. protein hydrolysate. The results of the protein hydrolyzate analysis showed that the degree of hydrolysis was 46.23%, the dissolved protein was 11.64% and the antioxidant activity was 549.16 ppm. Enzyme hydrolysis can increase dissolved protein content which is directly proportional to the increase in antioxidant activity.